Sleep disorders are associated with both morning temporal and jaw pain among adults and elderly: a population-based study in Brazil - Antônio Augusto SCHÄFER; Julia Niero Zanatta STRECK; Emilio Luiz STRECK; Micaela Rabelo QUADRA; Fernanda Oliveira MELLER (Faculdade São Leopoldo Mandic, 2023)
Objective Purpose: To assess the influence of sleep disorders on temporal and jaw pain in the morning in adults and elderly people. Methods: Population-based study with representative individuals aged 18 years or over. Individuals were selected using a multistage sampling procedure. The outcomes of morning jaw pain and morning temporal pain were assessed. Sleep bruxism, obstructive sleep apnea, and sleep quality were evaluated as exposure variables. Adjusted analysis was conducted using Poisson regression. All analysis was sex stratified. Results: 820 individuals were studied. Female with sleep bruxism were 1.37 times more likely to have morning temporal pain (p=0.041). Male and female with bruxism had a prevalence 160% and 97%, respectively, higher of morning jaw pain (male: p=0.003; female: p<0.001). Women with obstructive sleep apnea were 1.52 times more likely to have morning temporal pain (p=0.023). Men with poor sleep quality had a prevalence 190% higher of morning temporal pain (p=0.005). Conclusion: Morning craniofacial pain is more frequent in individuals with sleep disorders, and there are differences between sexes. Since more than one sleep disorder can be present in the same individual, studies that adjust the analyses for possible confounders are important to avoiding possible overlap between them.